If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + -2) + -5(3t + -2) = 25 + -6(5t + 4) Reorder the terms: 2(-2 + t) + -5(3t + -2) = 25 + -6(5t + 4) (-2 * 2 + t * 2) + -5(3t + -2) = 25 + -6(5t + 4) (-4 + 2t) + -5(3t + -2) = 25 + -6(5t + 4) Reorder the terms: -4 + 2t + -5(-2 + 3t) = 25 + -6(5t + 4) -4 + 2t + (-2 * -5 + 3t * -5) = 25 + -6(5t + 4) -4 + 2t + (10 + -15t) = 25 + -6(5t + 4) Reorder the terms: -4 + 10 + 2t + -15t = 25 + -6(5t + 4) Combine like terms: -4 + 10 = 6 6 + 2t + -15t = 25 + -6(5t + 4) Combine like terms: 2t + -15t = -13t 6 + -13t = 25 + -6(5t + 4) Reorder the terms: 6 + -13t = 25 + -6(4 + 5t) 6 + -13t = 25 + (4 * -6 + 5t * -6) 6 + -13t = 25 + (-24 + -30t) Combine like terms: 25 + -24 = 1 6 + -13t = 1 + -30t Solving 6 + -13t = 1 + -30t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '30t' to each side of the equation. 6 + -13t + 30t = 1 + -30t + 30t Combine like terms: -13t + 30t = 17t 6 + 17t = 1 + -30t + 30t Combine like terms: -30t + 30t = 0 6 + 17t = 1 + 0 6 + 17t = 1 Add '-6' to each side of the equation. 6 + -6 + 17t = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 17t = 1 + -6 17t = 1 + -6 Combine like terms: 1 + -6 = -5 17t = -5 Divide each side by '17'. t = -0.2941176471 Simplifying t = -0.2941176471
| 8x+12y=116 | | 7x+9=6x+3 | | 25+15x=10+20x | | 8-2(1a+1)=9+1a | | 5=5x+15 | | 10x-18=10.2+4x | | 2x-3+7x-9=7x+3-2x+9 | | 25x^2-y^2-25=0 | | 6(2x-7)=24 | | 3(5x+7)=51 | | 2(7x-6)=3+9x | | 154=(3n+6)+n | | 10w-5=3 | | 3fg-7f= | | 2x-44=10 | | x-.25x=708 | | 10x-45=11x+11 | | x^2+5x-24=0 | | f(x)=x^3-4x^2+6x | | x-.25x=780 | | f(x)=x^3-4x^2+6xes | | 931=7(12-4n) | | 5x-2(8x-4)=68-x | | x-.30x=850 | | 12x+10=14x-4 | | 5x+5-8=2(5x+8) | | 6x+7=8x+27 | | x^4+2x^3+320x=0 | | -3v+8=17 | | 84-x=4xm+7 | | -158=7(1+7m)+6m | | 2u-(-1)=-5 |